Contemplating space syntax and leadership in daycare settings - Dimkar, Ana (2016)
Space is an element in almost every organization that has not been observed nor studied in depth. Therefore, recent studies are taking many perspectives on space and examining its importance within the organization. In addition, the relation among space and leadership has been investigated. The intention is to show that the phenomenon of space has its importance in creating social relations in an organization, i.e. creates structure. Mixed methods of qualitative and quantitative approaches have been used to explore space in correlation to leadership in an organization as main focuses in the study. It was evident from the results that the kindergarten utilized the space in its greatest ability and the leadership has grown in a suitable style for the environment. An axial map and a visibility graph, respectively, showed the least and the most segregated spaces, and in comparison to structure, culture, and leadership, they showed the importance of utilizing space in accordance to the previously mentioned elements. Considering space as a social utility, a need to contribute to this notion was needed, and an investigation was undertaken. (It is a new leap in connecting the two phenomena of space and leadership through the prism of social relations.) However, there was no strong connection among space and relational leadership. The denouement of this study presents the importance of space as a decisive factor for structure and leadership in an organization.